Pengaruh Motivasi Kerja Terhadap Kinerja Tenaga Kependidikan Di SMA Negeri 18 Palembang - Aras Tulip; Indah Mawarni; Zein Ghozali; Arubina Bangsawan; Amalia Mustikatamara (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2019)
This study aims to determine the effect of work motivation the performance of educational staff at SMA Negeri 18 Palembang. The samples are 74 educational staff at SMA Negeri 18 Palembang. Technique of data collection is by distributing questionnaires to 7 4 respondents while the method used in this sampling is saturation sampling technique. The method of analysis uses IBM SPSS Statistics for Windows Version 24 program path. Based on the result of this study concluded that there is an effect of work motivation on the performance of SMA Negeri 18 Palembang educational stafs. As for suggestions that work motivation should be good, so that it can be further improved because it will give effect in improving the performance of educational staff at SMA Negeri 18 Palembang, where the higher the work motivation of educational staff, then the higher the performance will be.